2016
DOI: 10.3390/rs8050433
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability in Start and End of Growing Season in China Related to Climate Variability

Abstract: Satellite-derived vegetation phenophases are frequently used to study the response of ecosystems to climate change. However, limited studies have identified the common phenological variability across different climate and vegetation zones. Using NOAA/Advanced Very High Resolution Radiometer (AVHRR) Normalized Difference Vegetation Index (NDVI) dataset, we estimated start of growing season (SOS) and end of growing season (EOS) for Chinese vegetation during the period 1982-2012 based on the Midpoint method. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 67 publications
3
20
0
Order By: Relevance
“…Therefore, a longer duration of cooling, in days, is required at high altitudes to initiate a delayed EOS. This finding is consistent with other studies [71][72][73]. Crabbe et al [71] showed that warmer temperatures in extreme warm autumn events lead to significantly delayed EOS for needle leaf evergreen forest, broad-leaf deciduous forests, and mixed forests.…”
Section: Relationships Between Phenology Metrics and Climatic Factorssupporting
confidence: 91%
“…Therefore, a longer duration of cooling, in days, is required at high altitudes to initiate a delayed EOS. This finding is consistent with other studies [71][72][73]. Crabbe et al [71] showed that warmer temperatures in extreme warm autumn events lead to significantly delayed EOS for needle leaf evergreen forest, broad-leaf deciduous forests, and mixed forests.…”
Section: Relationships Between Phenology Metrics and Climatic Factorssupporting
confidence: 91%
“…Among the multiple preseason (here preseason refers to the period preceding a certain phonological date in which a climate factor has strongest impact on that phonology event; details are given in the method section) meteorological factors that could explain these changes, low temperature was identified as a major driver of leaf senescence in autumn (Cong, Shen, & Piao, ; Ding et al, ; Ge et al, ; Jeong et al, ; Liu, Fu, Zeng, et al, ; Liu, Fu, Zhu, et al, ; Marchand et al, ; Yang et al, ; Zeng et al, ; Zhao et al, ). In most of these studies, the interannual variations in the date of autumn phenology onset were related to daily mean temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true since the year 2000, a time during which China has experienced remarkably strong El Niño events [22]. Moreover, such research in China has mainly focused on SOS changes in temperate China [17,19,20,23]; to the best of our knowledge, few studies [20,24] have considered or discussed corresponding EOS or LOS changes. More importantly, previous studies of SOS within the Tibetan Plateau have reached contradictory conclusions [23,25] that appear to have depended on datasets or methodology.…”
Section: Introductionmentioning
confidence: 99%